Morocco in Other Words (Global Journal of Human-Social Science, 2015)
For many years now, questions of culture, race, sex and identity, among many others, have been coped with at length in Moroccan literary writings in different languages and for different purposes. These purposes, in fact, have been articulated in a variety of literary outlets with the aim of correcting cultural stereotypes, bridging cultural gaps to avoid cultural shocks or enlarging the extremes of intercultural dialogues among nations of the world. However, one such thorny question ought to be raised in this context is the extent to which any foreign language can be a resort to any Moroccan, in particular, and African writer, in general, to express the repressed cultural forms within their cultures. In this account, my contribution places under scrutiny the Moroccan text written in foreign languages, especially in English, as having the ability to translate the miscellaneous forms of the Moroccan cultural diversity to the outside world; a possibility which is now at hands more than ever before. To help capture this phenomenon in its contemporaneity, a combination of both Mikhail Bakhtin and Chantal Mouffe's philosophies is undertaken with the aim of laying bare the manifestation of a textual enterprise authored or co-authored by different voices in an in-between dialogical as well as virtual space.
Keywords: agonistic pluralism – dialogism – addressivity – answerability – expressivity – epistemic engagement – textual maneuver